Mewujudkan Kinerja Optimal Karyawan melalui Kepemimpinan Demokratis dan Lingkungan Kerja yang Kondusif : (Studi pada Kantor Pos Besar Yogyakarta) - Muskamal Muskamal; Syamsul Hadi; Ignatius Soni Kurniawan (EKONOMI DAN BISNIS DIGITAL, 2025)
This study aims to evaluate the influence of democratic leadership style and organizational environment on employee performance in the study of the Yogyakarta Post Office which is one of the state-owned companies in the service sector. Research data were collected from 85 employees of the Yogyakarta Post Office through a questionnaire with a quantitative approach using the survey method. Data analysis was carried out using multiple linear regression (SPSS). The results of the study showed that democratic leadership style and work environment have a positive and significant influence on employee performance. This proves that proactive leadership and a supportive work environment are key factors in improving employee performance. Therefore, organizations need to focus on human resource development, increasing adaptability, providing recognition, and implementing performance evaluations in order to create a more productive work environment and improve employee morale and overall performance.